A SWOT Analysis of the Hydroponics Entrepreneurship as Sustainable Income in Covid-19 Pandemic Adaptation - Glenn Pardede (Teknotan: Jurnal Industri Teknologi Pertanian, 2022)
The COVID-19 pandemic made us adapt to changes. One kind of adaptation that provides opportunities is hydroponics entrepreneurship as sustainable income generation. The sustainability context in this research is about how impactful hydroponics is with regard to economic, social and environmental aspects. This study aims to give a comprehensive understanding of the potential of hydroponics entrepreneurship, located in urban areas of Indonesia, as sustainable income generation. The research is a qualitative study that was conducted in Jakarta, Bogor, Depok, Tangerang and Bekasi. The data collection was conducted through literature review and in-depth interviews with 25 respondents. The literature review aims to give an understanding of the sustainability context while the interview focused on the Strength-Weakness-Opportunity-Threat (SWOT) analysis of hydroponics entrepreneurship activity. The findings of the interview show that the quality of hydroponics products and customer responsiveness in the two study areas may become the strengths of hydroponics. Meanwhile, the efficiency of production and innovation turn out as the weaknesses of the activities. Furthermore, the hydroponics grower can find opportunities in political, social, technological, and legal aspects, but they should be aware of the economic and environmental threats. In conclusion, hydroponics is a promising sector for income generation in the two study areas but considering both helpful aspects such as quality, customer responsive, technology, political environment, social condition, and legalization and harmful factors such as efficiency, innovation, economic condition, and environment are essential for the hydroponics growers.